Insights into impacts of temperature and organic load in anaerobic reactors treating effluents from fish processing industry - Camila de Aguiar Lima (2019)
The increase of fish production worldwide results in a consequent increase of generated effluents by processing industries. Due to its composition, this type of wastewater requires particular treatment solutions. Several alternatives have been suggested, such as the use of biological processes for the degradation of organic matter through microorganisms. However, studies on microbiome from anaerobic reactors sludge treating fish processing wastewater are still scarce. In order to evaluate temperature effects on anaerobic digestion treatment of fish processing effluents, replicated pilot-scale anaerobic reactors were operated at 20C and 37C for 60 days, being evaluated through physicochemical analysis and a metagenomic approach. The results demonstrated that 37C reactors were statistically superior from day 50 in chemical oxygen demand (COD) removal and the enrichment of hydrolytic and acidogenic Porphyromonadaceae, Rikenellaceae, and Spirochaetaceae families may have contributed to 37C reactors improved performance. However, to a better understanding of the process, a second experiment trial was designed to evaluate not only the temperature, but the influence of the applied organic load rate (OLR), which was done using the same methodology. In a different way, the 37°C reactors showed volatile fatty acids (VFA) accumulation, which lead to superior organic matter removal at 20°C. The Anaerobaculaceae family, present only at 37°C, was suggested as closely linked to high VFA levels in these reactors. Differently from the first trial, the main involved families in both temperatures were Ectothiorhodospiraceae, Syntrophorhabdaceae, Dethiosulfovibrionaceae and Synergistaceae, appearing with different abundances. Taking together, these results provide insights about the regulation of complex biological communities by temperature and OLR in anaerobic reactors used to treat fish processing wastewater.